Rapid estimation of excess mortality: nowcasting during the heatwave alert in England and Wales in June 2011. Issue 10 (5th July 2012) - Green, Helen K; Andrews, Nick J; Bickler, Graham; Pebody, Richard G
Abstract : Background: A Heat-Health Watch system has been established in England and Wales since 2004 as part of the national heatwave plan following the 2003 European-wide heatwave. One important element of this plan has been the development of a timely mortality surveillance system. This article reports the findings and timeliness of a daily mortality model used to 'nowcast' excess mortality (utilising incomplete surveillance data to estimate the number of deaths in near-real time) during a heatwave alert issued by the Met Office for regions in South and East England on 24 June 2011. Methods: Daily death registrations were corrected for reporting delays with historical data supplied by the General Registry Office. These corrected counts were compared with expected counts from an age-specific linear regression model to ascertain if any excess had occurred during the heatwave. Results: Excess mortality of 367 deaths was detected across England and Wales in ≥85-year-olds on 26 and 27 June 2011, coinciding with the period of elevated temperature. This excess was localised to the east of England and London. It was detected 3 days after the heatwave. Conclusion: A daily mortality model was sensitive and timely enough to rapidly detect a small excess, both, at national and regional levels. This tool will be useful when future events of public health significance occur.